The Impact of Translation Techniques on Shifting Meaning of Ordering Speech Act - Agustina Aloojaha; M. R. Nababan; Djatmika Djatmika (Bina Nusantara University, 2018)
This research was a follow-up research from some previous research which had discussed some imperative speech act, but it had not deeply discussed ordering speech act. The research aimed to find out the impact of translation techniques on shifting the meaning of ordering speech. The data were sentences which accommodate ordering speech act taken from the novel “Christ the Lord out of Egypt” and its translation in Indonesian taken from the novel “Kristus Tuhan Meninggalkan Mesir”. The data collected through document analysis, questionnaire, and forum group discussion (FGD). From the findings, there were 15 types of translation techniques which were used in translating, namely, established equivalent, variation, addition, implicit, explicit, adaptation, modulation, pure borrowing, generalization, particularization, transposition, reduction, paraphrase, discursive creation, and naturalized borrowing. The result indicates that the translation techniques that cause shifting meaning of ordering speech act are the addition, reduction, and discursive creation.